Expression of dna methylation of homeodomain transcription factor 2 (pitx2) and growth factor receptors in invasive ductal carcinoma of the breast - Wan Faiziah, Wan Abdul Rahman (Pusat Pengajian Sains Perubatan, 2013)
A paired-like homeodomain transcription factor 2 (PITX2) is another new marker in breast carcinoma when hypermethylation at P2 promoter of this gene was noted to be associated with poor prognostic factor. We investigated the expression of PITX2 protein using immunohistochemistry in invasive ductal carcinoma and its association with the established growth receptors such as ER, PR and HER2. We conducted a cross sectional study using 100 samples of archived formalin-fixed paraffin embedded tissue blocks of invasive ductal carcinoma and stained them with immunohistochemistry for PITX2, ER, PR and HER2. All HER2 with scoring of 2+ were confirmed with CISH. PITX2 protein was expressed in 53% of invasive ductal carcinoma and lack of PITX2 expression in 47%. Univariate analysis revealed a significant association between PITX2 expression with PR(p=0.001), ER(p=0.006), gland formation(p=0.044) and marginally associated with molecular subtypes of breast carcinoma (p=0.051). Combined ER and PR expression with PITX2 was also significantly associated (p=0.003) especially in double positive cases. Multivariate analysis showed the most significant association between PITX2 and PR (RR 4.105, 95%CI1. 765-9.547, p=0.001). PITX2 is another potential prognostic marker in breast carcinoma that able to add significant information to established prognostic factors of ER and PR. The expression of PITX2 together with PR may carry a very good prognosis.